Information security applications : 16th International Workshop, WISA 2015, Jeju Island, Korea, August 20-22, 2015, Revised Selected Papers /: 16th International Workshop, WISA 2015, Jeju Island, Korea, August 20-22, 2015, Revised Selected Papers. (2016) - Unknown
No abstract available